2015
DOI: 10.1016/j.rser.2015.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Progress and development in brick wall cooler storage system

Abstract: a b s t r a c tThis paper carried out a review study into the brick wall cooler storage system (zero energy storage) in terms of its originality, current status, research and implementation achievement, benefit and possible barriers. The continuous progress in technology innovation, heat and mass exchanger of the brick wall cooler storage system now varied from sand-zeolite mixture, volcanic plate made wall, natural ventilation for releasing excess inside relative humidity, optimization of watering operation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Spoilage was maximum in unvented poly bags under ambient and zero energy cool chamber conditions. Storing banana fruit in unvented poly bags at low temperature could extend the shelf-life of the fruit up to 19.33 days [7]. From the above studies, it can be seen that all of their ZECC was constructed on the surface.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Spoilage was maximum in unvented poly bags under ambient and zero energy cool chamber conditions. Storing banana fruit in unvented poly bags at low temperature could extend the shelf-life of the fruit up to 19.33 days [7]. From the above studies, it can be seen that all of their ZECC was constructed on the surface.…”
Section: Introductionmentioning
confidence: 94%
“…The design was based on the evaporative cooling of a porous body [1,7,9,10]. Two different of ZECC were constructed.…”
Section: Structure Of the Zeccmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the traditional post‐harvest technologies for controlling the release of ethylene gas from fruits may not be desirable. This is because present technologies tend to have high transportation and operation costs, energy demands, and potentially produce toxic chemicals . Ethylene removal using zeolite as an adsorbent has received considerable attention in both industry and agriculture application .…”
Section: Introductionmentioning
confidence: 99%
“…This is because present technologies tend to have high transportation and operation costs, energy demands, and potentially produce toxic chemicals. 3,[10][11][12][13][14] Ethylene removal using zeolite as an adsorbent has received considerable attention in both industry and agriculture application. [15][16][17][18] Trinh et al 16 compared the efficiency of three different zeolites for adsorbing ethylene from an air steam and showed that silver (1.0%)/13X zeolite had high ethylene adsorption affinity.…”
Section: Introductionmentioning
confidence: 99%